DINAMIKA KEHIDUPAN KELUARGA PASCA PERNIKAHAN KEDUA: PERAN, TANTANGAN DAN HUBUNGAN ORANGTUA SAMBUNG - Fatia Aulia Rahma; Nazwa Amalia (STKIP Subang, 2026)
Second marriage is an increasingly common phenomenon in society. This condition brings new dynamics within the family, especially in the relationship between the remarried couple, biological children, and stepchildren. This research aims to describe the roles, challenges, and efforts to build harmony in families following a second marriage using in-depth interview data. The findings show that family harmony is strongly influenced by communication, acceptance, understanding of each member’s character, and implementation of Islamic principles in daily life. Furthermore, spiritual motivation and commitment to perfecting life in this world and the hereafter play an essential role in maintaining family stability. Keywords: second marriage, step-parenting, family dynamics, muamalah.